Soccer endurance development in professionals - Roescher, C. R.; Elferink-Gemser, M. T.; Huijgen, B. C. H.; Visscher, C. (International Journal of Sports Medicine, 2010)
The development of intermittent endurance capacity, its underlying mechanisms and role in reaching professional level in soccer was investigated. The sample included 130 talented youth soccer players aged 14-18, who became professional (n=53) or non-professional (n=77) players in adulthood. In total 229 Interval Shuttle Run Test (ISRT) scores were taken over five years. Players who became professionals improved from age 14 to 18 on average from 68 to 109 runs in contrast to players who remained amateurs (from 73 to 93 runs). A longitudinal model was developed using linear mixed models procedures. Intermittent endurance capacity can be predicted adequately with a two-level hierarchical model (p<0.05). Anthropometric characteristics and playing position did not improve model fit (p>0.05). The estimated ISRT score necessary to reach professional level is: ISRT=-375.77-62.89+(51.20+4.20) * age-1.50 * age2+3.54 * hours of soccer training+1.18 * additional training hours. In conclusion, intermittent endurance capacity improves with age in talented youth soccer players. From age 15 players who reached the professional level show a faster development than their non-professional counterparts. This development is positively influenced by both soccer specific and additional training.